Digital storytelling of English advertisement in ESP teaching in Indonesia - Rizki Puji Lestari; Deli Nirmala (Universitas Islam Sultan Agung, 2020)
This paper discusses the benefits of by using digital storytelling in order to improve the polytechnic learners in learning activity of English for Specific Purposes. In this case, digital storytelling is used as advertising media for promoting agricultural products in English registered in Technology of Agricultural Product study program at PDD UNS, Indonesia. The subjects of this research were fourth semester learners of Technology of Agricultural Product in PDD UNS who followed English 2 class. The data were collected from the learners’ surveys and the video projects. The method of this research was descriptive qualitative research to evaluate the learners English public speaking in product advertisement by using digital storytelling. The result shows that digital storytelling is a useful learning approach to improve both non-linguistic skills and productive linguistic skills in English advertisement. There were some weaknesses of by using digital storytelling in English learning. The learners would have some difficulties if there was no internet access. Besides, electronic tools such as handycam or camera recorder is needed to record the video. Then, a video-editing skill also can be determining whether the video plot is good or not. According to the result which has shown above, it can be stated that the activeness of the learners depend on how the lecturer bring the material during teaching learning process. Through the attractive teaching method or technique, it can help the learners to build their self-confidence.